DIPLOMASI EKONOMI INDONESIA PADA PRESIDENSI G20 TAHUN 2022 TERHADAP PENINGKATAN INVESTASI ASING - Annajah, Fahriah, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
Economic problems are a complex issue worldwide, requiring countries to maintain stable national economic growth, including Indonesia. Indonesia is alo striving to improve the country’s economic stability, particulary by increasing foreign investment, a key pillar in boosting a country’s economic growth. In 2022, Indonesia was selected to host the G20 forum. To achieve stable national economic growth, especially post-pandemic, Indonesia is leveraging the momentum of its 2022 G20 presidency to implement economic diplomacy focused on increasing foreign direct investment, thereby enchancing the country’s economic stability. The results of the research indicate that Indonesia’s implementation of economic diplomacy during the 2022 G20 presidency has significantly influenced the increase in foreign direct investment in Indonesia across various sectors. Keywords: Economic Diplomacy, Foreign Direct Investment, G20, National Interest.